Punção aspirativa por agulha fina como meio de diagnóstico em cirurgia buco-maxilo-facial - Gonçalves , Sérgio Luiz Melo (2002)
The authors have done a retrospective analysis in the head and neck section of National Cancer lnstitute - RJ of 399 samples of fine needle aspirative biopsies (FNAB), which have been done on nodular lesions as well as in subcutaneous and submucosal lumps, all of them in the anatomical area of action of oral and maxillofacial surgery. The cytopathological results of the FNAB were compared with the histopathological results which, statistically showed indexes of precision of 95,66%, excluding the samples considered insatisfactory for diagnosis (7,52%). We have found 15 false-negatives results and just one false-positive (88,46% of sensitivity and 99,58% of specificity indexes). So, this thecnic of aspirative biopsy was satisfactory in early and redirectionable diagnosis in neoplasic and noneoplasic lesions, besides its feasible facilities, high precision, low costs and almost free of complications.